Developing Students’ Thinking Through Problem Solving In Mathematics (The Peerian Journal, 2026)
This article extensively covers the role and importance of mathematical problems in the development of independent thinking of students in the process of teaching mathematics in the primary education system. During the study, the educational, educational and developmental aspects of mathematical problems were analyzed, and special attention was paid to the issues of forming students' logical, creative and critical thinking through the use of reallife problems. Also, ways of developing students' independent decision-making skills by solving problems in various ways are revealed. The article is of practical importance for primary school teachers and students of the pedagogical direction.